Consensus Guidelines for Management of Congenital Cataract in Pakistan - Muhammad Moin, Mian Muhammad Shafique (Pakistan Journal of Ophthalmology, 2018)
Purpose: To formulate guidelines for management of congenital cataract in Pakistan through consensus of Pediatric Ophthalmologists. Study Design: Mixed methods study using Delphi technique. Place and Duration of Study: Study was conducted among pediatric ophthalmologists of the Ophthalmological Society of Pakistan from June 2016 to February 2017. Material and Methods: A survey questionnaire was constructed containing 40 questions after literature review, which covered almost all aspects of the management of congenital cataract. This survey was answered by 56 renowned pediatric ophthalmologists of Pakistan using the survey monkey online program. The analyzed data was presented in a planned face-to-face meeting of top 15 members of the Association of Pediatric Ophthalmology, Pakistan. The data was discussed point by point and consensus was built with some additions and modifications. Results: 41 out of 56 pediatric ophthalmologists answered the survey. The most common presentation of a child with congenital cataract in our study was white pupil (72%) and 97.5% participants said that repeat eye examination should be done after dilation of pupil to confirm the diagnosis. 77% participants felt that the child should not be operated if cataract opacity is smaller than 3 mm. In our country, only one-third of the pediatric ophthalmologists were in favor of implanting intraocular lens (IOL) by the age of one year but there was 80% consensus to do so by the age of 2 years. Children with dense cataract should be operated by 2 months of age according to 80% participants. It is preferred to perform primary posterior capsulotomy with or without anterior vitrectomy in all children who undergo congenital cataract surgery in any age until 5years (87%). Conclusion: Management of congenital cataract by pediatric ophthalmologists in Pakistan is consistent with internationally available guidelines. Key words: Congenital cataract, Consensus, Guidelines, Management.